Primary hepatic neuroendocrine tumor associated with hypertension: A case report - Zhao, Bin; Mao, Jie; Li, Yumin (Frontiers in Surgery, 2023)
Background: Primary neuroendocrine tumors are exceedingly rare and often misdiagnosed. The combined methods of ultrasonography, computed tomography (CT) and magnetic resonance imaging (MRI) are typically applied. The diagnosis of the disease mainly depends on the histopathological examination. Surgical resection is the most effective treatment. Case presentation: In the report, we describe the case of a patient with a primary hepatic neuroendocrine tumor (PHNET) associated with hypertension. The patient suffered from uncontrolled hypertension before the operation, and the blood pressure was not well controlled by oral antihypertensive drugs such as nifedipine, valsartan and hydrochlorothiazide, but the patient's blood pressure completely returned to normal after the operation. Conclusions: We encountered a rare case of a PHNET associated with hypertension via careful screening noticed by the patient at work; furthermore, we hope to collect more cases and find the relationship between neuroendocrine tumors and hypertension.